Relationship between ascites volume and clinical outcomes in epithelial ovarian cancer. Issue 4 (27th January 2021) - Quan, Quan; Zhou, Shuwei; Liu, Yao; Yin, Wanchun; Liao, Qianqian; Ren, Siling; Zhang, Fenfen; Meng, Yu; Mu, Xiaoling
Abstract: Objective: Ascites is a tumor microenvironment, ascites and massive ascites‐induce compression could promote the progression of epithelial ovarian cancer (EOC); however, the impact of ascites volume on clinical outcomes has not been studied extensively. We aimed to investigate the association between ascites volume and clinical outcomes especially platinum resistance in EOC. Methods: We retrospectively evaluated a total of 546 EOC patients with respect to the amount of ascites, clinicopathologic factors, and survival. Using the threshold of 1500 ml to classify patients into small‐ and large‐volume ascites groups, we analyzed the correlation between ascites volume and clinicopathological factors, including platinum‐free interval (PFI), and prognosis. Results: Patients with large volume ascites were more likely to present with later stage disease, primary platinum‐resistant (PPR) cancer, and suboptimal cytoreduction. Prolonged PFI was associated with decreased ascites volume. The large‐volume ascites group showed worse progression‐free survival (PFS) and overall survival (OS). An increase in ascites volume was associated with an increased risk of disease recurrence (hazard ratio [HR] = 1.115, 95% confidence interval [CI]: 1.035–1.200) and death (HR = 1.213, 95% CI: 1.090–1.350). Conclusions: Ascites was an independent predictor of PFS and OS in EOC patients. A large volume of ascites predicated a shortened PFI, an increased incidence of PPR and suboptimal cytoreduction. Thus, the volume of ascites is a simply available clinical parameter, which could be used to evaluate the prognosis and platinum resistance of EOC patients early, it contributes to formulate individualized treatment plan and improve the outcome of EOC patients.